Psychological Well-Being of an English Lecturer in Managing Academic and Teaching Demands: A Narrative Study - Tira Nur Fitria (Universitas Kristen Cipta Wacana, 2026)
This study explores and understands the psychological well-being of English language lecturers in managing academic and teaching demands through a narrative inquiry approach. Specifically, this research aims to identify internal and external factors influencing lecturers’ psychological well-being and to understand how these experiences shape their professional identity, resilience, and meaning-making within the context of higher education. The narrative findings show that English lecturers’ psychological well-being is a dynamic condition shaped by the interaction between internal psychological resources and external academic environments. Heavy and overlapping academic roles—teaching, research, administration, and service—create sustained workload pressure, emotional exhaustion, and blurred work–life boundaries, with administrative demands emerging as a major source of stress. Discipline-specific challenges in English teaching further intensify emotional labor, although meaningful teaching experiences and student progress serve as important protective factors. Internal resources such as motivation, resilience, self-efficacy, emotional regulation, reflective practice, and meaning-making help lecturers manage academic pressures and maintain professional commitment. While, external factors, including workload policies, leadership support, collegial relationships, teaching conditions, and institutional support systems, strongly influence whether demands are perceived as manageable or overwhelming. Overall, psychological well-being develops through continuous negotiation between personal coping capacities and organizational conditions, highlighting the need for both individual and institutional approaches to support English lecturers’ well-being. Understanding lecturers’ lived experiences enables institutions to design well-being–oriented policies and support systems. A holistic approach that combines institutional support with the strengthening of lecturers’ internal coping resources is essential to promote sustainable well-being, enhance teaching quality, and ensure long-term professional commitment.